An analysis of common calcaneal tendon disruption in canids - Foster, Sophie, author (Colorado State University. Libraries, 2024)
My senior honors thesis project, "An Analysis of Common Calcaneal Tendon Disruption in Canids," aims to demonstrate knowledge of a prevalent condition seen in veterinary medicine. This project consists of a literature review analyzing common calcaneal tendon disruption in canines that describes the anatomy, etiology, prevalence, symptoms, diagnostics, and associated treatments. To accompany the literature review are two skeletal articulations showcasing a real-life example of the canine anatomy relevant to this condition. One articulation is the caudal end (or back end) and a canine, which includes the right and left pelvic limbs, the pelvis, and the lumbar and caudal vertebrae. Another articulation of a canine pelvic limb was created as a model to imitate the common calcaneal tendon and demonstrate an avulsion, or detachment, from its bony insertion point. This model will be given to the animal anatomy lab at CSU to assist with student learning. Lastly, a presentation highlighting all of the information and material gathered throughout this project was created and shared with faculty. After completing this project, I have become much more knowledgeable on common calcaneal tendon disruptions in canines and more familiar with the process of articulating skeletal models. I am very grateful for this opportunity and all the experiences that have led me to this moment!
College of Veterinary Medicine and Biomedical Sciences.